2023
DOI: 10.1146/annurev-environ-112522-072642
|View full text |Cite
|
Sign up to set email alerts
|

Plastics and the Environment

I.E. Napper,
R.C. Thompson

Abstract: Plastics are persistent and pervasive throughout the environment and have now been reported from the deepest parts of the ocean to the tops of the highest and most remote mountains. There is a body of information on the sources, degradation, and transport of plastics as well as a variety of research investigating the ecotoxicological and wider ecological consequences of plastic ingestion and accumulation. Such knowledge has been obtained with developments in field and laboratory methods for plastic identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 182 publications
1
11
0
Order By: Relevance
“…14 However, it is crucial to note that MPs leachates can also inhibit microbial activity. 31,53 In general, our meta-analysis results indicated that MPs significantly increased DOC, which is in line with the recent meta-analysis. 16 However, another global meta-analysis showed that MPs' presence does not significantly increase DOC.…”
Section: Overall Effect Of Mps On Soil Csupporting
confidence: 91%
See 2 more Smart Citations
“…14 However, it is crucial to note that MPs leachates can also inhibit microbial activity. 31,53 In general, our meta-analysis results indicated that MPs significantly increased DOC, which is in line with the recent meta-analysis. 16 However, another global meta-analysis showed that MPs' presence does not significantly increase DOC.…”
Section: Overall Effect Of Mps On Soil Csupporting
confidence: 91%
“…MPs, as a great C source, at least the leachates coming from the particles, can be absorbed by soil microbes, thereby contributing to increased soil microbial biomass . However, it is crucial to note that MPs leachates can also inhibit microbial activity. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires studies that allow us to anticipate the potential impacts of plastic pollution on organims. In the context of global change, microplastics have not yet been identified as a threat to pollination. , However, evidence suggests that microplastics are intrinsic environmental components that alter plant reproduction. , Determining how microplastics move in the environment and their concentrations in soils, air, animals, and plants is essential for advancing our knowledge of this issue and developing effective strategies to mitigate their harmful effects on plant reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…The global demand for plastic products which are considered essential in daily life results in an annual production of a huge amount of plastics (exceeding 380 million tons). [1][2][3][4][5] However, due to the non-degradability, these plastics pose a great threat to the ecological environment and may even endanger human's health or animal's life. [6] Those that enter the environment are hard to degrade because of the strong covalent bonding on the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%